Calculators Topics Go Premium About Snapxam
ENGESP
Topics

Step-by-step Solution

Solve the trigonometric equation $\frac{x-3}{2}=\frac{6}{x-2}$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$\frac{x-3}{2}=\frac{6}{x-2}$

Learn how to solve trigonometric equations problems step by step online.

$\left(x-3\right)\left(x-2\right)=12$

Unlock this full step-by-step solution!

Learn how to solve trigonometric equations problems step by step online. Solve the trigonometric equation (x-3)/2=6/(x-2). Apply fraction cross-multiplication. Solve the product \left(x-3\right)\left(x-2\right). Moving the term 6 to the other side of the equation with opposite sign. Rewrite the equation.

Answer

$x=6,\:x=-1$

Problem Analysis

$\frac{x-3}{2}=\frac{6}{x-2}$

Related formulas:

1. See formulas

Time to solve it:

~ 0.04 seconds